A new species of Simiolus from the middle Miocene of the Tugen Hills, Kenya. Issue 125 (December 2018) - Rossie, James B.; Hill, Andrew
Abstract: A new species of the "small-bodied ape" Simiolus is described here that extends the temporal range of the genus to the end of the Middle Miocene. As such, it is one of the few species of fossil primates known from East Africa during a time of significant change in which Old World monkeys and crown hominoids replaced the primitive ape-like primates that had dominated the early Miocene. The dynamics of this important event in our evolutionary history are obscured by the small number of fossil primates known from Africa between 14 and 6 million years ago, as well as persistent ambiguity regarding the phylogenetic status of the ape-like Miocene primates. The new species described here helps to fill this temporal gap, and our analysis of its phylogenetic position suggests that Simiolus and many other Miocene primates were not only ape-like, they were, indeed, stem hominoids. Judging from the available material, the new species may be the smallest known ape.